2018
DOI: 10.1111/jnc.14620
|View full text |Cite
|
Sign up to set email alerts
|

Role of βarrestin1 in AT1R‐mediated mitogen‐activated protein kinase activation in Wistar and SHR brainstem astrocytes

Abstract: barrestin (barr)-1 and -2 are ubiquitously (outside the retina) expressed G-protein-coupled receptor adapter proteins. They uncouple G-protein-coupled receptors from G proteins, internalize the receptor, and subsequently initiate their own wave of signaling independently of G proteins. Angiotensin (Ang) II type 1 receptor (AT 1 R) is a well-established example of a receptor signaling through barrs. Despite the pivotal role of brain AT 1 Rs in the regulation of blood pressure, the involvement of barr-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The mechanisms proposed include reduction in MAPK pathways such as ERK1/2-and p38-phosphorylation. 79 We showed that ICV infusion of TRV027 increased the aversion to saline (ie, decreased saline preference) and lowered blood pressure in the deoxycorticosterone acetate-salt model of hypertension. 81 Further, studies of β-arrestin-1-deficient or β-arrestin-2-deficient mice revealed that deleting β-arrestin-2 stimulates an increase in saline intake and augments the pressor response to deoxycorticosterone acetate-salt hypertension.…”
Section: At 1 R β-Arrestin and Blood Pressurementioning
confidence: 91%
See 2 more Smart Citations
“…The mechanisms proposed include reduction in MAPK pathways such as ERK1/2-and p38-phosphorylation. 79 We showed that ICV infusion of TRV027 increased the aversion to saline (ie, decreased saline preference) and lowered blood pressure in the deoxycorticosterone acetate-salt model of hypertension. 81 Further, studies of β-arrestin-1-deficient or β-arrestin-2-deficient mice revealed that deleting β-arrestin-2 stimulates an increase in saline intake and augments the pressor response to deoxycorticosterone acetate-salt hypertension.…”
Section: At 1 R β-Arrestin and Blood Pressurementioning
confidence: 91%
“…Other studies have also demonstrated that spontaneous hypertensive rat brainstem astrocytes display lower levels of β-arrestin1. 79 Further, overexpression of β-arrestin1 in the rostral ventrolateral medulla (located in the brainstem) of spontaneous hypertensive rats lowered BP with no effect in normotensive controls. 80 Different nuclei in the brainstem are known as key regions for the production, regulation and activation of RAS component.…”
Section: At 1 R β-Arrestin and Blood Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…β-arrestin signaling induced by AT1R activation in astrocytes might contribute to central control of blood pressure and may be implicated in the pathophysiology of hypertension, given the fact that AT1R signaling through β-arrestins may be involved in the regulation of angiotensinogen production by these cells ( Negussie et al, 2019 ).…”
Section: Mechanisms Of Gpcr Signaling Diversificationmentioning
confidence: 99%